Makna Tradisi Tampung Tawar Membangun Rumah Dalam Suku Dayak Ngaju - Sibarani, Roy Andreo Admajaya; Ahad, Desi Natalia; Sanasintani; Ni Nyoman Astrini Utami (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2023)
This research aims to show the tradition of tampung tawar which is a custom/tradition carried out until now by the Ngaju Dayak tribe. This tradition has a meaning to soothe the owner of the new house and dwelling. Specifically, this research will bring together an understanding of the symbolic meaning of the actions of the Christian Dayak Ngaju community in the text of Genesis 1:1. The researcher used a descriptive qualitative method. Data was obtained specifically discussing the tradition of tampung tawar in building houses in the Christian Ngaju Dayak tribe, both from field data (observations and interviews), as well as from books, journals, or from encyclopedias or dictionaries. The results show that the tradition of tampung tawar and the symbols of some of the requirements and materials that must be followed and prepared to build a house provide a deep and meaningful meaning for those who build a house. Everything on this earth is God's creation. Everything He created is good, including the tampung tawar, the materials/symbols used. Symbols have a very important meaning in culture, because symbols are representatives of the world. This can be seen in the daily lives of individuals.